MON-LB083 The Dimorphic Effects of Short-Term Dietary Changes on the Central and Circulating IGF1 System in Rats - Guerra Cantera, Santiago (J Endocr Soc, 2019)
The insulin like-growth factor (IGF) system is involved in numerous physiological functions including growth, development, metabolism, longevity, and neuroprotection. Obesity alters the peripheral IGF1 system, but its effects on the central IGF1 system or whether dietary factors have direct effects on this system remains unclear. Moreover, little is known about the metabolic regulation of the newest members of this family, the pappalysins (PAPP-A) and stanniocalcins (STCs). In rodent obesity models, both chow and low-fat diets (LFD) are used as controls when studying the effects of high-fat diet (HFD) intake, but commercial LFDs contain high levels of sucrose that could trigger metabolic alterations. We hypothesized that short-term HFD and LFD consumption differentially modify the central and circulating IGF1 systems. Adult male and female Wistar rats were given a HFD (60% fat, 8.9% sucrose, 5.1 kcal/g) or LFD (10% fat, 33.1% sucrose, 3.76 kcal/g) or maintained on a normal rodent chow (3.1 % fat, 0.9% sucrose, 3.41 kcal/g) for 1 week. Serum hormone levels were measured by ELISA and tissue gene expression by RT-qPCR. HFD increased body weight (p<0.05) exclusively in males. Males had higher serum levels of free and total IGF1, IGF-binding protein (BP) 3, IGFBP5, insulin, leptin and triglycerides compared to females (p<0.001) and PAPP-A2 was higher in females (p<0.05). There was no effect of diet. In males, the hypothalamic mRNA levels of IGF2 (p<0.01) and IGFBP2 (p<0.001) increased after LFD intake compared to both chow diet and HFD, with no effect in females. No effects were found on the remaining members of the IGF1 system analyzed (IGF1, IGF1R, IGFBP3-5, PAPP-A and STC-2). In males, the LFD also increased the mRNA levels of neuropeptide-Y (p<0.01) and Agouti-related peptide (p<0.05) compared both to chow and HFD, with no effect in females. No changes were observed in POMC and CART mRNA levels in either sex. The hypothalamic changes in males in response to LFD could result from the high sucrose levels in this diet. The LFD-induced increase in hypothalamic IGF2 and IGFBP2 observed only in males suggests that these factors may be involved in the metabolic response to this diet in a sexually-dimorphic manner. Unless otherwise noted, all abstracts presented at ENDO are embargoed until the date and time of presentation. For oral presentations, the abstracts are embargoed until the session begins. Abstracts presented at a news conference are embargoed until the date and time of the news conference. The Endocrine Society reserves the right to lift the embargo on specific abstracts that are selected for promotion prior to or during ENDO.